New therapeutic and diagnostic opportunities for injured tissue-specific targeting of complement inhibitors and imaging modalities. Issue 3 (June 2016) - Holers, V. Michael; Tomlinson, Stephen; Kulik, Liudmila; Atkinson, Carl; Rohrer, Bärbel; Banda, Nirmal; Thurman, Joshua M.
Abstract: Despite substantial opportunity and commercial interest in developing drugs that modulate the complement system in a broad range of non-orphan indications, several obstacles remain to be overcome. Among these issues is the biophysical nature of complement proteins, whose circulating levels are typically very high and whose turnover rates are relatively rapid, especially in the setting of chronic inflammatory conditions. This situation necessitates the use of very high levels of therapeutic compounds in order to achieve both multi-pathway and multiple effector mechanism inhibition. In addition, one must avoid infectious complications or the systemic impairment of the other important physiological functions of complement. Herein we focus on the development of a novel therapeutic strategy based on injured tissue-specific targeting of complement inhibitors using the antigen-combining domains of a small subset of natural IgM antibodies, which as endogenous antibodies specifically recognize sites of local damage across a broad range of tissues and locally activate complement C3, resulting in C3 fragment covalent fixation. Because the use of such recombinant tissue-targeting inhibitors precludes the utility of measuring systemic levels of complement biomarkers or function, since a goal of this targeting strategy is to leave those processes intact and unimpeded, we also briefly describe a new method designed to quantitatively measure using imaging modalities the inhibition of generation of fixed C3 fragments at sites of inflammation/injury. In addition to the ability to determine whether complement activation is locally constrained with the use of inhibitors, there is also a broader application of this imaging approach to inflammatory and autoimmune diseases characterized by local complement activation.